Characterization and simulation of graphite edge surfaces for the analysis of carbonaceous material separation from sulfide ores by flotation. (31st May 2022) - Sime, Freddy M.; Jin, Jiaqi; Wang, Xuming; Wick, Collin D.; Miller, Jan D.
Highlights: HOPG edge surface analysis helps to explain the flotation behavior of CM. Multiscale disorders (Raman) and polar O species (XPS) identified at HOPG edge. Oxidation of graphite edge surfaces simulated by ab-initio method. Simulated oxidized graphite edge surfaces completely wetted by MD water drop. Experimental SEM images of face roll-over at HOPG edges explain 40° contact angle. Abstract: The efficient processing of base metal sulfide ores and sulfidic gold ores is sometimes compromised by the presence of carbonaceous material (CM). One common way of dealing with the CM problem is to pre-float the CM before the flotation of the sulfide minerals. Most CM exhibits some crypto crystalline graphitic structure. Although the graphite face surface has been studied extensively and is well described, the structural and surface properties of the graphite edge surface are more complex. In this study, the surface topography, graphitic structure, and functional features of the highly ordered pyrolytic graphite (HOPG) edge surface are reported to help provide a fundamental understanding of the behavior of CM in sulfide flotation separations. Surface structural defects, disordered atomic structure, and polar groups (C-O and C=O) were found from Scanning Electron Microscopy (SEM), Atomic Force Microscopy (AFM), Raman, and X-ray Photoelectron Spectroscopy (XPS) analyses. The armchair and zigzag edge surfaces of graphite have been examined by ab-initio and Molecular Dynamics (MD) simulation to describe the experimental results, including wetting characteristics based on contact angle measurements. Polar oxygen species, such as C-O-C and C=O bonds, were identified during oxidation of the graphite edge surfaces by ab-initio simulation of the surface reaction with oxygen molecules. MD simulations indicated complete wetting of the simulated oxidized graphite edge surfaces by water, whereas previous experimental contact angle measurements at the HOPG edge surface (40°) revealed some hydrophobic character, which indicate the complex heterogenous nature of the edge surfaces.